1996
DOI: 10.1089/oli.1.1996.6.119
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Photomodification of Single-Stranded DNA Targets by Arylazide and Perfluoroarylazide Derivatives of Oligonucleotides

Abstract: Highly efficient site-specific photomodification of single-stranded DNA targets was achieved with oligonucleotide reagents bearing aromatic azido groups (R (R1 = p-azidotetrafluorobenzoyl, R2 = 2-nitro-5-azidobenzoyl, R3 = p-azidobenzoyl) at either the terminal phosphate or at the C5 position of deoxyuridine at the end or inside of the oligonucleotide chain. The extent of modification strongly depends on the reagent type. It does not exceed 5% in the case of the reagent with R3. It was 25%-50% and 60%-70% for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Preparation of Plasmid DNA − NLS Peptide Conjugates. Diazocoupling ( ) and photoactiviation ( ) have been reported as the covalent modifications of DNA. In this study plasmid DNA−NLS peptide conjugates were prepared by the diazo coupling method according with Scheme .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Preparation of Plasmid DNA − NLS Peptide Conjugates. Diazocoupling ( ) and photoactiviation ( ) have been reported as the covalent modifications of DNA. In this study plasmid DNA−NLS peptide conjugates were prepared by the diazo coupling method according with Scheme .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…66 In addition, the acceptor fluorine atoms increase the electrophilicity of the singlet nitrene 10-fold 67 and reactivities of the triplet nitrene and the azacycloheptatetraene, 1000 and 10 000-fold, respectively, 68 in comparison with nonfluorinated derivatives. Dobrikov et al 46,47 studied the effect of the aryl azide structure on the efficiency of site-specific photomodification of DNA by comparing the reactivities of oligonucleotide derivatives of 4-azido-, 5-azido-2-nitro-and 4-azidotetrafluorobenzamides. Upon irradiation with UV light, these compounds generate different species, viz., azacycloheptatetraene 32, the triplet (33) and the singlet (31) nitrenes, respectively; the yields of covalent adducts in site-specific photomodification were 5%, 15% and 70%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of modification products with piperidine showed that the degree of modification of these residues was * 50%, the largest degree of modification being 40%, 45%, 45% and 65%, respectively. 46,47,69 The reactions of the singlet nitrene 31 with the nitrogen atoms of the pyridine type of the heterocycles result in N-amination (Scheme 3). Photomodification of ss-DNA is most probably accompanied by electrophilic addition at position N(7) of guanine.…”
Section: Methodsmentioning
confidence: 99%
“…This is an active intermediate which is able to provide a high yield of cross-links with both nucleic acids and proteins under a short (less than 1 min) irradiation, using commercially available UV-lamps. [47][48][49] The excellent cross-linking properties of perfluorated aryl azides relates to the higher reactivity of the respective nitrenes as compared to those of the unfluorinated aryl azides. 50 Secondly, the ATB group can be introduced at various nucleotide positions not involved in classical Watson-Crick base-pairing, namely, at the C5 of uridines, N7 of guanosines or C8 of adenosines, in addition to the 59-or 39-terminal phosphates (Fig.…”
Section: Derivatives Of Oligoribonucleotides Modified With Perfluorop...mentioning
confidence: 99%